Beyond the scene: graphic humor, censorship and repression in the play "Liberdade, Liberdade" (Tempo e Argumento, 2022)
This paper aims to analyze the show Freedom, freedom through the relations between graphic humor and theater during the Brazilian dictatorship. The play premiered in Rio de Janeiro in 1965, by Flávio Rangel and Millôr Fernandes. It was produced by Grupo Opinião and in its first season many names from the Brazilian cultural art scene starred at the play: Paulo Autran, Nara Leão, Oduvaldo Viana Filho and Tereza Raquel. Throughout its trajectory, issues arised with censorship, paramilitary forces and the high echelon of the dictatorial government. Before this complex scenario, the objective of this article will be to understand some aspects of the show by analyzing the relationship of the play and graphic humor, both in the play itself and in the press. Using the caricature included in the play program and published cartoons in the newspapers Correio da Manhã and Última Hora, we seek to demonstrate that cartoonists appropriated the play to create blunt critics of the military regime. Through these sources we intend to analyze at least three elements: 1) the use of humor as a visual and narrative strategy; 2) the difficulties faced by the State to establish censorship criteria; 3) the denunciation of the paramilitary actions suffered by the play. The hypothesis is that this type of document will allow the investigation of the play’s impact within the cultural field of resistance to the regime, as well as its reverberations in the press and in the government.
Keywords: military dictatorship; theater; political humor; caricature